Socio-political root of economic crisis of Sri Lanka in 2022 - Santhirasegaram, S (Journal of Bangladesh Institute of Planners, 2023)
The main objective of this study is to investigate the relationship between economics and other social science disciplines, including sociology and political science, in relation to the current economic crisis in Sri Lanka. Qualitative and quantitative data demonstrate that the current economic crisis in Sri Lanka is an outcome of socio-political unrest with civil war between and within the communities from 1983 to 2021. Observation, key person interviews, and statistical (correlation and regression) analyses of time series data from 1983 and 2021 show that Sri Lanka's overall macroeconomic stability, measured by six macroeconomic variables altogether, is positively correlated with socio-political stability, measured by a proxy of percentage change of tourist arrivals with a correlation coefficient of 0.52. One percentage change in socio-political stability leads to a 0.35 percent increase in macroeconomic stability. Effects of socio-political instability are more significant than openness and economic policy in the determination of overall macroeconomic stability. The interviews with subject experts confirm these findings. Policymakers in Sri Lanka have to correct past ethnic policies and bring permanent peace and socio-political solidarity between and within the communities before economic policy reforms to secure the economy from crisis. JBIP, Vol. 16, 2023, pp. 40-52